ANALISIS PERHITUNGAN, PENYETORAN, PELAPORAN, DAN PENCATATAN PAJAK PENGHASILAN PASAL 21 ATAS PEGAWAI TETAP PADA PT X - LYDIA CHRISTIANA HERYANTO; WILLIEM CHAHYA WIJAYA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this study is to analyze the suitability calculations, payment and reporting of Income Tax 21 made by the company with the tax regulations. The study also compare the amount of income tax payable 21 PT X with PER 31 / PJ / 2012 and PER 32 / PJ / 2015 as a result of the change in taxable income. Data of this study consisted of payroll, list income tax calculation Article 21, SPT Masa PPh Article 21, the evidence reported Income Tax Article 21. This study discusses the calculation, payment, reporting and recording of Income Tax Article 21 PT X and comparison calculations with PER 31 / PJ / 2012 and PER 32 / PJ / 2015. Descriptive analysis method used for this study, where the study is conducted by collecting data and information related to the calculation, payment, reporting, and recording of Income Tax Article 21. The result of this research is the calculation, payment, and tax reporting in 2015 by PT X is not in accordance with the tax regulations. In reporting PT X there some reporting are delays. PT X in the calculation and reporting of payroll and income tax article 21 2015 in accordance with the method of gross-up can be seen from the SPT 1771 Board Annual annex I point 5 appears deferred admission fee. The change of taxable income, causing the overpayment that the correction made directly from January to June and compensation to reduce taxes in July.